Risk Factors Associated with Severe Macromastia among Adolescents and Young Women. Issue 6 (15th September 2022) - Massey, Gabrielle G.; Firriolo, Joseph M.; Nuzzi, Laura C.; Pramanick, Tannishtha; Malloy, Shannon M.; DiVasta, Amy D.; Labow, Brian I.
Abstract : Background: Macromastia is common among adolescents and young women and has well-documented negative physical and psychosocial effects. The pathogenesis of idiopathic macromastia has been attributed to increased end organ sensitivity to circulating gonadal hormones. Despite the known negative effects of macromastia, there is a paucity of literature examining the clinical risk factors associated with macromastia severity in this age group. Methods: In this cross-sectional study, standardized clinical forms were administered to patients between the ages of 12 and 21 years undergoing reduction mammaplasty. Data were collected pertaining to patient demographics, biometrics, breast symptoms, medical and family history, and breast tissue resection mass at the time of reduction. Resection mass was normalized to patient body surface area in analyses. Results: A total of 375 patients were included in analyses. Mean age at surgery was 18.1 years. The following risk factors were positively associated with macromastia severity in both univariate and multivariate logistic regression models: overweight or obesity, racial or ethnic minority status, patient-reported gynecologic or endocrine complaints, and early menarche ( p < 0.05, all). More severe cases of macromastia were associated with approximately three times the odds of being overweight or obese or achieving menarche before 11 years old. Conclusions: In our sample, overweight or obesity, racial or ethnic minority status, early menarche, and patient-reported gynecologic or endocrine complaints were all positively associated with macromastia severity. Awareness of these factors can empower physicians to identify and address modifiable risk factors to prevent progression to more severe disease. Macromastia itself should prompt screening for gynecologic or endocrine complaints with referral as indicated. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.